Histochemical Studies on the Lung of Goat Foetuses (Capra hircus) - Sharma, Vikas (Indian Journal of Veterinary Anatomy, 2018)
The columnar lining epithelial cells of the developing airways were strongly reactive to glycogen and contained glycogen granules at their apical parts in the lung of the goat fetuses in group-I. However, the reaction was diminished withadvancing age of the goat fetuses. Similar trend was seen in regard to neutral and acidic mucopolyssacharides. But the reaction was reverse in regard to basic proteins as the reaction was gradually intensive in the columnar cells in older goat fetuses. In the present investigation, fat particles could not be detected in any  histocompartment of the lungs of all the goat fetuses.